IMPLEMENTASI PRODUK PEMBIAYAAN UMKM DI BSI KCP KAJEN PEKALONGAN - Ria Kusmawati Ria Kusmawati (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2022)
Islamic banking is an economic institution that operates in the economic sector. Where this is banking has an important role in moving the wheels of the community's economy to become a better society and have quality human resources. This study aims to explain the practice of implementing financing products for the micro business segment at Bank Syariah Indonesia and strategies in increasing MSME financing at Bank Syariah Indonesia in order to realize the welfare of the community. The research uses a descriptive-qualitative methodology where the data used are primary and secondary data. Primary data was obtained by conducting interviews while secondary data was obtained from various literatures such as books, internet, journals and previous research. The results of this study can be formulated regarding the implementation of financing for the micro business segment at Indonesian Islamic Banks and strategies to increase MSME financing in Islamic Banks.